2020
DOI: 10.20944/preprints202003.0469.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of a Simplified Radiometric Calibration Framework for Water-Based and Rapid Deployment Unmanned Aerial System (UAS) Operations

Abstract: The current study sets out to develop an empirical line method (ELM) radiometric calibration framework for reducing atmospheric contributions in UAS imagery and for producing scaled remote sensing reflectance imagery. Using a MicaSense RedEdge camera flown on a custom-built octocopter, the research reported herein finds that atmospheric contributions have an important impact on UAS imagery. Data collected over the Lower Pearl River Estuary in Mississippi during five week-long missions covering a wide range of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Use of ELM calibration is probably the most commonly used method of radiometric calibration of airborne remote sensing data (Poncet et al, 2019), and it has been thoroughly reviewed (Smith and Milton, 1999;Baugh and Groeneveld, 2008;Aasen et al, 2018). Several studies have provided important insight into practical use and repeatability of ELM calibration (Che and Price, 1992;Smith and Milton, 1999;Karpouzli and Malthus, 2003;Wang and Myint, 2015;Aasen et al, 2018;Iqbal et al, 2018;Mafanya et al, 2018;Agapiou, 2020;Zarzar et al, 2020). Experimental data from this study showed its considerable sensitivity to time of day (sun parameters and weather variables).…”
Section: Elm Calibrationmentioning
confidence: 76%
See 4 more Smart Citations
“…Use of ELM calibration is probably the most commonly used method of radiometric calibration of airborne remote sensing data (Poncet et al, 2019), and it has been thoroughly reviewed (Smith and Milton, 1999;Baugh and Groeneveld, 2008;Aasen et al, 2018). Several studies have provided important insight into practical use and repeatability of ELM calibration (Che and Price, 1992;Smith and Milton, 1999;Karpouzli and Malthus, 2003;Wang and Myint, 2015;Aasen et al, 2018;Iqbal et al, 2018;Mafanya et al, 2018;Agapiou, 2020;Zarzar et al, 2020). Experimental data from this study showed its considerable sensitivity to time of day (sun parameters and weather variables).…”
Section: Elm Calibrationmentioning
confidence: 76%
“…However, flying at higher altitudes means reduction in spatial resolution and therefore increase in mixed pixels, and that may adversely affect radiometric repeatability. Zarzar et al (2020) acquired drone-based remote sensing data from grey calibration boards at nine altitudes ranging from 4 -244 m, and they developed an ELM calibration framework to maximize radiometric repeatability based on atmospheric correction. The study by Zarzar et al (2020) was based on remote sensing data acquired during multiple flight missions over the course of a full year, and goodness of fit values for three spectral bands were: R 2 -green = 0.77, R 2 -red = 0.79, and R 2 -nir = 0.77).…”
Section: Studies Of Radiometric Repeatabilitymentioning
confidence: 99%
See 3 more Smart Citations